Incremento do valor da arrecadação de ICMS na economia cearense com a adoção do regime de substituição tributária: estudo de caso no setor industrial de calçados - Matos Filho, Joaquim Messias (2012)
The present work has as its principal aim to analyze the impact of the Tributary Substitution regime of the collection of ICMS in the industrial sector of Ceará, through a case study in the footwear sector, whose collection of taxes has been realized since 2006 by the cited regime, through Decree No. 28326 of 25/07/06. The Tributary Substitution institute of the segment in analysis came to be used rather than normal regime, in view of its facility to control a larger number of companies, assigning to a responsible the collection of the entire commercialization chain. We used a information database from the Department of Finance of the State of Ceará (Sefaz- Ce) and we used the Differences in Differences methodology considering a control group - companies that remained in the normal regime of taxes collection; and a treatment group - companies that passed to the Tributary Substitution. After the analysis we perceive a positive impact of 24,38% of collection in the footwear industry, for the considered period from 2003 to 2009.